Apple Museum of Technology Interior with Eclectic Style. - Muhammad Ardhiansyh; Thomas Kristianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2015)
Apple as a brand that is known so elegant and always futuristic in grain products is a media education requires a bridge or a real facility that can be realized with a public facilities such as museums, so that the messages that is sufficient to educate and inspire the next young generation in the future, apart from the product - Apple product itself, can be received intact and correctly on the application later. Mediating the messages through a public facilities such as a museum with eclectic style, can dig some of Apples own vision The mission related to education and technology and a history that has meaning and studies enough to be known by the people in the world , in addition to generation - the younger generation that will come. See Apple from another point of view (History), is another way also in the approach to the users of the Apple products worldwide. In this case, there are some reviews that could answer some of the questions that are considered to be a public dilemma in todays technological world market, that is how a technology product can be so loved and became a lifestyle that is quite closely attached to the human behavior, as well as how a technology can inspire and can make the man himself makes a change and revolution against something in this world. Then, at the end concluded that the word museum, a public facility that media could be one charger the charge as a study material which have been mentioned above.